2017
DOI: 10.1038/s41598-017-11384-w
|View full text |Cite
|
Sign up to set email alerts
|

Virome analysis for identification of novel mammalian viruses in bats from Southeast China

Abstract: Bats have been shown as important mammal resevoirs to carry a variety of zoonotic pathogens. To analyze pathogenic species in bats from southeast coastal regions of China, we performed metagenomic sequencing technology for high throughput sequencing of six sentinels from southeast coastal area of China. We obtained 5,990,261 high quality reads from intestine and lung tissue of 235 bats, including 2,975,371 assembled sequences. 631,490 reads predicted overlapping sequences for the open reading frame (ORF), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 40 publications
2
59
2
Order By: Relevance
“…Although most of the infected animals tested positive in the intestines (81.8%-9/11), in two animals, CoV was only detected in other organs (lungs and liver), raising the chances of viral detection. Other authors have also reported the presence of CoV RNA in tissues and secretions other than intestines or fecal samples, such as kidney, heart, lungs, and oropharyngeal swabs [25,55,56]. However, this is the first report of BtCoV detection in the liver.…”
Section: Discussionmentioning
confidence: 73%
“…Although most of the infected animals tested positive in the intestines (81.8%-9/11), in two animals, CoV was only detected in other organs (lungs and liver), raising the chances of viral detection. Other authors have also reported the presence of CoV RNA in tissues and secretions other than intestines or fecal samples, such as kidney, heart, lungs, and oropharyngeal swabs [25,55,56]. However, this is the first report of BtCoV detection in the liver.…”
Section: Discussionmentioning
confidence: 73%
“…In Brazil, BtAdV has been detected in Desmodus rotundus, the most common vampire bat in Brazil [16]. Papillomaviruses (PVs), which are also dsDNA viruses, have also been reported in diverse bats species [17][18][19], but so far, they have not been reported in bats in Brazil. Parvoviruses, a family of single-stranded DNA (ssDNA) viruses that exhibits the highest mutation rate among DNA viruses [9] have been reported worldwide, including in Brazil [20] and have been shown to be related to human-infecting parvoviruses [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…RNA extraction and RT-PCR analysis. All samples were pooled and then underwent reverse transcription PCR analysis as previously described 36 . Briefly, each intestine sample (~0.1 g) was homogenized www.nature.com/scientificreports www.nature.com/scientificreports/ using a glass grinder with 10 volumes of SM buffer (50 mM Tris, 10 mM MgSO4, 0.1 M NaCl, pH7.5).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, several novel bat-associated viruses in southeast China were annotated through metagenomic sequencing technology 36 , including coronavirus, norovirus, adenovirus, bocavirus, astrovirus, circovirus, and adeno-associated viruses. To date, there have been no adeno-associated virus studies in the coastal areas of Southeast China.…”
mentioning
confidence: 99%